The Impact of ChatGPT Usage on Students Digital Communication - Rina Manggalani; Candra Kusuma; Metta Novianti; Troi Bao Tang (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2026)
This study aims to investigate the effect of ChatGPT usage on students' digital communication competence. Despite the increasing adoption of ChatGPT in higher education, empirical studies examining its influence on students' digital communication competence remain limited. A quantitative survey approach was employed involving eighth-semester students at STIAB Jinarakkhita Lampung. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and simple linear regression using SPSS. Digital communication competence was measured through students' ability to access, evaluate, and communicate information effectively and ethically in digital environments. The findings reveal that ChatGPT usage has a positive and significant influence on students' digital communication competence. Students who use ChatGPT more effectively tend to demonstrate better abilities in information processing, digital message construction, and ethical digital communication. This study concludes that ChatGPT can serve as a valuable educational tool for strengthening students' digital communication competence when integrated responsibly into higher education. The findings contribute to the growing literature on AI-assisted learning and provide practical implications for the effective integration of generative AI in higher education.